2011
DOI: 10.1007/s10549-011-1837-z
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67: level of evidence and methodological considerations for its role in the clinical management of breast cancer: analytical and critical review

Abstract: Clinicians can use biomarkers to guide therapeutic decisions in estrogen receptor positive (ER+) breast cancer. One such biomarker is cellular proliferation as evaluated by Ki-67. This biomarker has been extensively studied and is easily assayed by histopathologists but it is not currently accepted as a standard. This review focuses on its prognostic and predictive value, and on methodological considerations for its measurement and the cut-points used for treatment decision. Data describing study design, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
189
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(205 citation statements)
references
References 110 publications
5
189
1
7
Order By: Relevance
“…The reason is that despite data indicating the correlation between high ki67 and pCR, most of these data are derived from retrospective studies other than clinical trials [6][7][8][9][10][11]. Furthermore, Ki67 cutpoints used in these studies were selected empirically (with thresholds associated with the mean of observed values in the study population) or were arbitrarily established at 10%-25% [14].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that despite data indicating the correlation between high ki67 and pCR, most of these data are derived from retrospective studies other than clinical trials [6][7][8][9][10][11]. Furthermore, Ki67 cutpoints used in these studies were selected empirically (with thresholds associated with the mean of observed values in the study population) or were arbitrarily established at 10%-25% [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is not predictive for chemotherapy, but high Ki-67 was found to be associated with immediate complete response in the neoadjuvant setting (Luporsi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation is often assessed by immunohistochemistry using Ki-67. This protein is present during all active phases of the cell cycle, including G1, S, G2, and mitosis (Luporsi et al, 2011), while in mitotic count, only those cells which are in the mitotic phase are counted. Since breast cancer has a prolonged doubling time (Medina et al, 2011), we can conclude that in the proliferation (mitotic activity index) method, the S phase is identified earlier than other phases, while the mitotic forms are identified later.…”
Section: Discussionmentioning
confidence: 99%